Associations between long-term exercise participation and lower limb joint and whole-bone geometry in young and older adults - Scorcelletti, Matteo; Zange, Jochen; Böcker, Jonas; Sies, Wolfram; Lau, Patrick; Mittag, Uwe; Reeves, Neil D.; Ireland, Alex; Rittweger, Jörn (Frontiers in Physiology, 2023)
Features of lower limb bone geometry are associated with movement kinematics and clinical outcomes including fractures and osteoarthritis. Therefore, it is important to identify their determinants. Lower limb geometry changes dramatically during development, partly due to adaptation to the forces experienced during physical activity. However, the effects of adulthood physical activity on lower limb geometry, and subsequent associations with muscle function are relatively unexplored. 43 adult males were recruited; 10 young (20-35y) trained i.e., regional to world-class athletes, 12 young sedentary, 10 older (60-75y) trained and 11 older sedentary. Skeletal hip and lower limb geometry including acetabular coverage and version angle, total and regional femoral torsion, femoral and tibial lateral and frontal bowing, and frontal plane lower limb alignment were assessed using magnetic resonance imaging. Muscle function was assessed recording peak power and force of jumping and hopping using mechanography. Associations between age, training status and geometry were assessed using multiple linear regression, whilst associations between geometry and muscle function were assessed by linear mixed effects models with adjustment for age and training. Trained individuals had 2° (95%CI:0.6°-3.8°; p=0.009) higher femoral frontal bowing and older individuals had 2.2° (95%CI:0.8-3.7°; p=0.005) greater lateral bowing. An age-by-training interaction indicated 4° (95%CI:1.4°-7.1°; p=0.005) greater acetabular version angle in younger trained individuals only. Lower limb geometry was not associated with muscle function (p>0.05). The ability to alter skeletal geometry via exercise in adulthood appears limited, especially in epiphyseal regions. Furthermore, lower limb geometry does not appear to be associated with muscle function.